Mechanical properties of hybridized kenaf/chitosan fibres reinforced polyethylene biocomposites - Shamsuri, Ahmad Adlie; Tan, Muhammad IzzuddinSyariff (Journal of Scientific and Engineering Research, 2017)
In this research, natural fibre such as kenaf core fibre (KCF) was used as filler for preparation of the biocomposites. Low-density polyethylene (LDPE) has been selected as a polymer matrix for preparation of the biocomposites due to its low production cost. Besides that, chitosan was used as secondary filler to investigate its effect on mechanical properties of the prepared biocomposites. Brabender internal mixer was used to composite the materials at temperature of 150°C. The process was taken about 15 minutes to complete the compositing. After that, the biocomposites were moulded into sheet with 1 mm thickness by using compression moulding machine at 150 °C for 2 minutes. Then, the samples were cut into dumbbell and rectangular shapes to perform tensile and impact tests, respectively. For tensile test, the machine used was Instron universal testing machine which done according to the ASTM D638-10, while for impact test, the machine utilised was Instron impact testing machine which conducted in accordance with the ASTM D256-10. The results of tensile stress,tensile modulus, tensile strain and impact strength were recorded and analysed at the end of the tests.